Level of Effectiveness and Seriousness on The Problems Encountered in the Implementation of Crime Prevention Strategies of The Philippine Na-tional Police in Olongapo City, Philippines - Binan, Generico M.; Dausan, Alrien Francisco; Echaure , Jessie Sabellano (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
Every country is impacted by criminality on an economic, social, and political level. The national news in the Philippines typically reports on crimes against persons and property because of the prevailing belief that the country's economic standing is insufficient to support an individual's level of living. The Philippine National Police (PNP) in Olongapo City has not yet succeeded in implementing crime prevention and control, despite their best efforts to prevent crime. The Philippines uses foreign approaches to crime prevention that don't align with the nation's current criminality issues. The PNP organization is facing difficulty in crime prevention due to its inability to demonstrate its efficacy and efficiency in the performance of its duty. The primary aspect that leads to the prevention of crime is following the path of morality, virtue, and ethics by all the individuals. These morals and values would enable a person to focus on the achievement of his life and career goals and abstain from conducting any kind of criminal and violent acts.